High performance materials and devices for high-speed electronic systems - Jain, F; Broadbridge, C; Tang, H; Gherasimova, M (World Scientific Publishing Co. Pte. Ltd., 2018)
In this review volume, the editors have included the state-of-the-art research and development in nano composites, and optical electronics written by experts in the field. In addition, it also covers applications for emerging technologies in High-Speed Electronics. In summary, topics covered in this volume includes various aspects of high performance materials and devices for implementing High-Speed Electronic systems. © 2019 by World Scientific Publishing Co. Pte. Ltd. All rights reserved.
Keywords: Emerging technologies; High performance material; High-speed electronics; Materials; Nanocomposites; Optical electronics; State of the art; dept.phy

Preface - Jain, F.; Broadbridge, C.; Tang, H.; Gherasimova, M. (International Journal of High Speed Electronics and Systems, 2018)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (International Journal of High Speed Electronics and Systems, 2018)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy